Development of molecular markers and a diagnostic tool for investigation of coinfections by and interactions between potato purple top and potato witches'‐broom phytoplasmas in tomato. (1st October 2015) - Wei, W.; Wu, W.; Davis, R.E.; Lee, I.‐M.; Zhao, Y.
Abstract: Columbia Basin potato purple top (PPT) phytoplasma and Alaska potato witches'‐broom (PWB) phytoplasma are two closely related but mutually distinct pathogenic bacteria that infect potato and other vegetable crops. Inhabiting phloem sieve elements and being transmitted by phloem‐feeding insect vectors, both pathogens are affiliated with ' Candidatus Phytoplasma trifolii' and are members of the clover proliferation phytoplasma group (16SrVI). The polyphagous nature and wide geographic distribution of their insect vectors make mixed infection inevitable. In this study, we experimentally constituted a simultaneous PPT and PWB phytoplasma infection in tomato ( Solanum lycopersicum ) and developed a sensitive diagnostic tool to investigate mixed infections by and in planta interactions of the two phytoplasmas. The distribution and relative abundance of the two co‐infecting phytoplasmas were monitored over a 45‐day post‐infection time course and for three serial passages in planta . Our results revealed that dual infections of the two phytoplasmas induce a new symptom unseen in infection by either phytoplasma alone. Our results also raised an interesting question as to whether the two phytoplasmas differ in ability of competitive dominance under co‐infection conditions. The molecular markers and the diagnostic tool devised in this study should be useful for further investigations of the interactions between the two closely related phytoplasmas in their hosts.